PENGETAHUAN REMAJA PUTRI TENTANG INFEKSI MENULAR SEKSUALDI KELURAHAN SANGAJI KECAMATAN TERNATE UTARA - Muhammad, Rusny (Jurnal Kesehatan Poltekkes Ternate, 2014)
ABSTRACT: Young Women Overview Knowledge About Sexually Transmitted Infections in the Village District of North Ternate Sangaji 2014 (Supervised by Rusny Muhammad And Nur Eda Mansur). Infeksi Menular Seksual (IMS) are diseases that are transmitted through sexual intercourse . Indonesia , sexually transmitted infections are most commonly found are syphilis and gonorrhea . The prevalence of sexually transmitted infections in Indonesia is very high is found in the city of Bandung , Surabaya , and Jakarta . The survey results were received by Badan Koordinasi Keluarga Berencana ( BKKBN ) in 2008 , there were 63 % of adolescents in Indonesia between the ages of middle and high school already had sexual intercourse outside marriage . Impact on adolescent sexual behavior resulted in many teenagers are infected with an STI. The purpose of this study was to Looking Young Women Overview Knowledge About Sexually Transmitted Infections in the Village District of North Ternate Sangaji 2014 ". This research is descriptive Analytical approach cross section . This study was carried on in the Village District of North Ternate Sangaji on 20 January to 1 February 2014 . With a sample of 82 respondents and a sampling technique that Quota Sampling . The instrument used was a questionnaire enclosed , while the techniques of data analysis using univariate analysis. The results showed the level of knowledge of adolescents about sexually transmitted infections in the Village District of North Ternate Sangaji that adolescents who have a good knowledge of 40 respondents ( 48.8 % ) , knowledge quite as many as 34 respondents ( 41.4 % ), and lack of knowledge as much as 8 respondents (9.8 %)